Khat use and related determinants among pregnant women within Haramaya, Ethiopia: a mixed methods study - Wood, Elizabeth A.; Stark, Heather; Case, Stuart J.; Sousa, Barbara; Moreno, Melanie; Motuma, Aboma; Wilfong, Tara (Frontiers in Global Women's Health, 2024)
Introduction Khat, a green leafy plant grown in East Africa and throughout the Arabian Peninsula, is chewed for its psychoactive and amphetamine-like effects, serving as a significant aspect of culture, economic livelihood, and global trade. Khat consumption during pregnancy has been associated with adverse effects, including anemia, premature rupture of membranes, and low birth weight, among others. Methods This cross-sectional, explanatory sequential mixed methods study was conducted in the Haramaya District of eastern Ethiopia using a questionnaire and focus group discussions. Questionnaires assessed socio-demographic information, pregnancy history, and diet, including khat use. Data were analyzed using SPSS v28 to include descriptive statistics, proportions, odds ratios, binary logistic regression, and chi-square analysis. FGDs expanded on the knowledge, attitudes, and practices of khat in the region, including pregnant or lactating women from two different kebeles. Two independent reviewers conducted a qualitative content analysis to examine the qualitative findings from the FGDs. Transcripts from the focus groups were entered into NVivo 14 to aid in capturing salient themes. Results A total of 444 pregnant women with a median age of 25 years completed the questionnaire. Two-thirds of the women, 66.9%, reported currently consuming khat while pregnant, and 72.7% of them reported daily consumption. The FGD analysis resulted in the discovery of five themes: Economic Livelihood, Maternal Significance, Medicinal Implications of Khat, Pesticide Use, and Social and Cultural Applications. Discussion This study revealed an alarming high prevalence of khat consumption among pregnant women in the Haramaya District, highlighting the pressing need for long-term studies to assess the health consequences. The role of khat as both an economic staple and an energy source for daily activities underscores the challenges in curbing its use. The documented health risks associated with the chemicals used in khat cultivation, including cancer, call for interventions to enhance safe agricultural practices in households involved in khat farming.